THE ROLE OF INFORMATION TECHNOLOGIES IN INCLUSIVE EDUCATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Inclusive education serves as an important tool in ensuring the integration of children with disabilities into society. With the help of information technologies, it is possible to adapt the educational process, teach on the basis of an individual approach, and effectively use educational resources. This article analyzes the methods of using information technologies in inclusive education and their effectiveness.